Differential Modulation of Annexin I Binding Sites on Monocytes and Neutrophils. Issue 1 (1999) - Euzger, H. S.; Flower, R. J.; Goulding, N. J.; Perretti, M.
Abstract : Specific binding sites for the anti-inflammatory protein annexin I have been detected on the surface of human monocytes and polymorphonuclear leukocytes (PMN). These binding sites are proteinaceous in nature and are sensitive to cleavage by the proteolytic enzymes trypsin, collagenase, elastase and cathepsin G. When monocytes and PMN were isolated independently from peripheral blood, only the monocytes exhibited constitutive annexin I binding. However PMN acquired the capacity to bind annexin I following co-culture with monocytes. PMN incubation with sodium azide, but not protease inhibitors, partially blocked this process. A similar increase in annexin I binding capacity was also detected in PMN following adhesion to endothelial monolayers. We propose that a juxtacrine activation rather than a cleavage-mediated transfer is involved in this process. Removal of annexin I binding sites from monocytes with elastase rendered monocytes functionally insensitive to full length annexin I or to the annexin I-derived pharmacophore, peptide Ac2-26, assessed as suppression of the respiratory burst. These data indicate that the annexin I binding site on phagocytic cells may have an important function in the feedback control of the inflammatory response and their loss through cleavage could potentiate such responses.